Innovation, Growth and Competitiveness Dynamic Regions in the Knowledge-Based World Economy - Nijkamp, Peter; Siedschlag, Iulia (Advances in Spatial Science, The Regional Science Series, 2011)
This book investigates dynamic regions in the context of greater global interaction in a world economy increasingly driven by knowledge and innovation. It offers novel empirical evidence on the underlying factors of the growth performance of these spaces. In particular, the following questions are addressed: What role is there for research, education and innovation in the development strategies of the dynamic growth regions? What are the risks and consequences of dynamic growth on patterns of world growth and development, competitiveness, inequalities, and convergence? What development strategies should be promoted at national and international levels to promote a growing and more sustainable world economy? What are the implications of the emerging new competitors for Europe?s competitiveness? Using an innovative, integrated framework of analysis, the contributions in this book combine a wide array of complex theoretical and methodological approaches.